ChemInform Abstract: An Efficient Method for the Preparation of Dialkoxymethanes from Dichloromethane with Alcohols Catalyzed by a Cu‐NHC Complex. Issue 52 (6th December 2016) - Zhan, Lewu; Pan, Renming; Xing, Ping; Jiang, Biao
Abstract: The title synthesis is successfully performed using benzylic, heterobenzylic or aliphatic alcohols as well as phenol or catechol as the substrates.